Perlindungan Hukum Untuk Pemegang Hak Atas Tanah Dengan Kasus Sertifikat Ganda Atas Sebidang Tanah Di Badan Pertanahan Nasional - Ginting, Sejahtera Imanuel; Idham, Idham (Universitas Medan Area, 2021)
Use of land without rights is prohibited. Therefore, there must be the issuance of a certificate of land rights. However, in practice, there is still circulation of land rights that are not in accordance with the provisions of the legislation and one of them is the circulation of cases of overlapping ownership of a plot of land in the community. The issuance of multiple lands by the land office results in dual land certificates, which contradicts land rights controlled by individuals and the principle of legal certainty, legal entities or institutions. This article discusses the forms of protection and legal remedies for land holders, rights regarding several certificate disputes. Based on the study, in practice, the law on the protection of land rights holders is regulated in Article 32 of Government Regulation number 24 of 1997 concerning Land Registration that legal efforts to settle land disputes that can be taken by holders of dual land rights who are harmed can take an out of court/non-judicial route. litigation and litigation/litigation. This article ends with suggestions for real reforms from the bureaucracy of the National Defense Agency and improving the quality of human resources and must know in advance the status of land ownership rights in the event of a transaction in terms of the transfer of land ownership rights so as not to cause problems in the future.